The Impact of Emotion-focused Therapy on Anxiety and Depression among Female-Headed Households in Imam Khomeini Relief Committee - Marjan Khosravi Asl; Mansoureh Nasirian; Alireza Bakhshayesh (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: The female-headed householdsare the most vulnerable members of society and since this population statum experiences a degree of emotional distress, the common signs and symptoms of anxiety and depression, Emotion-focused therapy, an empirically supported, neo-humanistic approach that integrates and updates person-centered, Gestalt, and existential therapy with a focus on emotional processing processes, has received condiferable ecperimental support. Methods: the aim of this study was to investigate the effect of emotion-focused therapy on the anxiety and depression of female-headed households.  Results: The results indicated that the emotion-focused therapy was effective on anxiety and depression among female- headed households (P <0.001). It was also observed that emotion-focused therapy can be used to reduce anxiety and depression. Conclusion: research was carried out by adopting a semi-experimental method and was administered through a pre-test post-test control group design. The statistical population consisted of all female-headed households in Imam Khomeini Relief Committee of Yazd in 2016. Among women who agreed to participate in the study (ranging from 25 to 50 years old), a number of women who gained a high score in the Beck Anxiety and Depression Inventory were selected by convenient sampling method. Then, 30 subjects were selected randomly and were assigned into two experimental groups (n=15) and a control group (n=15). This study employed instrument along with sociological information of subjects. The data were analyzed using covariance analysis.